Finding Nearest Mosque Using Haversine Formula on Android Platform - Setyorini, Indah; Ramayanti, Desi (JOIN (Jurnal Online Informatika), 2019)
Prayer is the second pillar of Islam, emphasized after the two sentences of syahadat. It's regarded as perfect worship. Obligatory for both Mukimin and Musafir, its virtue in the mosque equals 20 degrees of reward compared to elsewhere. However, amidst increasing traffic jams, travelers often face difficulty finding the nearest mosque for Maghrib prayer. This problem can be addressed by finding the shortest path from the starting point to the destination. To tackle this issue, a research was conducted to design an application providing directions to the nearest mosque in the Larangan area of Tangerang city. The system utilizes the haversine formula and Java programming language for implementation. Java builds the application, MySQL database stores data, and Google Maps API determines the route.